Fairness-based altruism - Yves Breitmoser; Pauline Vorjohann (Bielefeld University, Center for Mathematical Economics (IMW), 2022)
Why do people give when asked, but prefer not to be asked, and even take when possible? We introduce a novel analytical framework that allows us to express context dependence and narrow bracketing axiomatically. We then derive the utility representation of distributive preferences additionally obeying standard axioms such as separability and scaling invariance. Such preferences admit a generalized prospect-theoretical utility representation reminiscent of fairnessbased altruism. As in prospect theory, the underlying preferences are reference dependent and non-convex, which directly predicts the previously irreconcilable empirical evidence on giving, sorting, and taking. We test the model quantitatively on data from seminal experiments and observe significantly improved fit in relation to existing models, both in-sample and out-ofsample.
urn:nbn:de:0070-pub-29629356
Keywords: C91; D64; D03; 330; Social preferences; axiomatic foundation; robustness; giving; charitable donations